THE PROTECTION OF HUMAN RIGHTS FOR THE ASIAN DIASPORA IN SOUTHEAST ASIA AND ERADICATION MAFIA OF TRADE PEOPLE - Ma’rifah Ma’rifah; Muhammad Najmi Fajri (Fakultas Hukum UVAYA Banjarmasin, 2022)
The Indonesian Diaspora Reality, which is a networked Community and strengthens with the potential of human resources which, not only is large, but